Stable operating limits and improvement methods for hydropower and photovoltaic integration through MMC-HVDC systems - Peng, Maolan; Feng, Lei; Zhang, Shuwen; Zhao, Wei (Frontiers in Electronics, 2024)
Quantitatively identifying the stable operating limit of MMC-HVDC system with large-scale renewable energy integration is of paramount importance for enhancing the capacity to integrate new energy. In this paper, the steady-state mathematical model and state-space model of bundled hydropower and photovoltaic integration through MMC-HVDC system are established. By considering both steady-state constraints and small-signal stability constraint, a novel method for computing the stable operating region of the system is proposed. Then the variations in the steady-state and smallsignal stability constraint boundaries under different short-circuit capacities of AC system are quantitatively assessed. The result reveals that as the short-circuit capacity of AC system decreases, the small-signal stability constraints further restrict the stable operating region of the system. Through eigenvalue analysis and participation factor analysis, the key factors influencing small-signal stability in weak AC system are investigated. To broaden the stable operating region of the system, a supplementary frequency damping control strategy is proposed. Finally, the theoretical analysis and calculation results are validated by building a simulation model for the bundled hydropower and photovoltaic integration through MMC-HVDC system in PSCAD/EMTDC.